The Transformation of Economic Structure in Palu City - Zubair, Muchammad; Jaya, Andi Herman; Lutfi, Muhtar; Sading, Yunus; Rafika, Ika (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Sustainable economic growth requires structural transformation to enhance the competitiveness of leading sectors in a region. This research aims to analyze the structural transformation of Palu City's economy from 2019 to 2024 using Location Quotient (LQ) and Shift-Share Analysis (SSA) analytical tools. The research results show that sectors such as Construction, Wholesale and Retail Trade, and Information and Communication have LQ values greater than 1 and contribute significantly to Palu City's GRDP. Conversely, the Agriculture and Manufacturing sectors reflect challenges in maintaining competitiveness. Results from Shift-Share Analysis reveal that the Information and Communication, Trade and Construction sectors remain the main pillars in post-disaster economic recovery, despite decreases in some components. This research contributes to understanding Palu City's economic transformation and provides a foundation for more effective economic development policies.